Microsoft PowerPoint 2013 plain & simple - Muir, Nancy 1954- (O'Reilly Media, Inc., 2013)
Get the guide that makes learning Microsoft PowerPoint 2013 plain and simple! This full color, no-nonsense book shows you the quickest ways to solve a problem or learn a skill, using easy-to-follow steps and concise, straightforward language. You'll analyze, manage, and share information in more ways than ever before. Here's WHAT you'll learn: Create dynamic presentations for your audience Include charts, tables, clip art, and other graphics Add video clips and CD music Animate slide and add transition effects Edit and polish your presentations with ease Create speaker notes and record narration Here's HOW you'll learn it: Jump in whenever you need answers Easy-to-follow STEPS and SCREENSHOTS show exactly what to do Handy TIPS teach new techniques and shortcuts Quick TRY THIS! Exercises help apply what you learn right away.
Includes index. - Description based on online resource; title from PDF title page (ebrary, viewed October 9, 2013)
Keywords: Microsoft PowerPoint (Computer file); Presentation graphics software